2018
DOI: 10.1002/cmdc.201800617
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Synthesis of Complex Spiro[3H‐indole‐3,2′‐pyrrolidin]‐2(1H)‐ones by Intramolecular Cyclization of Azomethine Ylides: Highly Potent MDM2–p53 Inhibitors

Abstract: Mouse double minute 2 (MDM2) is a main and direct inhibitor of the crucial tumor suppressor p53. Reports from initial clinical trials showed that blocking this interaction with a small‐molecule inhibitor can have great value in the treatment of cancer for patients with p53 wild‐type tumors; however, it also revealed dose‐limiting hematological toxicities and drug‐induced resistance as main issues. To overcome the former, an inhibitor with superior potency and pharmacokinetic properties to ultimately achieve fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It is interesting to note that all the subtly different binding modes for compound 18 arise from a rotation of the iso-indolinone with the privileged indole scaffold remain fixed in all structures. Structural rigidification of the bond between the indole and iso-indolinone resulting in natural product-like structures similar to the approach we took with mdm2 [34] should lead to an improvement of both potency and selectivity. It should be noted that all the observed SI/II-pocket interactions, including those with bound water molecules, have not yet been successfully addressed with one molecule.…”
Section: Future Perspectivementioning
confidence: 98%
“…It is interesting to note that all the subtly different binding modes for compound 18 arise from a rotation of the iso-indolinone with the privileged indole scaffold remain fixed in all structures. Structural rigidification of the bond between the indole and iso-indolinone resulting in natural product-like structures similar to the approach we took with mdm2 [34] should lead to an improvement of both potency and selectivity. It should be noted that all the observed SI/II-pocket interactions, including those with bound water molecules, have not yet been successfully addressed with one molecule.…”
Section: Future Perspectivementioning
confidence: 98%
“…We applied a three component [3 + 2] cycloaddition for the synthesis of 2 and reported a novel intramolecular cycloaddition for compounds 3 and 4 (Figure ). , Aiming for further potency and improvement of PK properties, we found that the rigidified fused-indazole motive (Scheme ) had promising properties and optimized this series to obtain 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As explained in the introduction, and demonstrated in many recent works, these type of spiro-derivatives are able to disrupt the interaction between MDM2 and p53, which is the origin of their anti-proliferative action [53,54]. Therefore, we performed computational studies on our substrates 5a – d to focus mainly on their behaviour as disruptors of MDM2–p53 complex and to predict their activity.…”
Section: Resultsmentioning
confidence: 99%